The synthesis of lysylfluoromethanes and their properties as inhibitors of trypsin, plasmin and cathepsin B. - Angliker, H (1987)
The synthesis of two lysylfluoromethanes is described by an extension of the synthesis method of Rauber, Angliker, Walker & Shaw [(1986) Biochem. J. 239, 633-640]. Ala-Phe-Lys-CH2F was found to be an active-centre-directed inhibitor of plasmin and trypsin, as is the corresponding chloromethane. However, the rate of covalent-bond formation is about an order of magnitude lower at 25 degrees C for the fluoro derivative. It was, in addition, an extremely effective inactivator of cathepsin B at pH 5.4 and 6.4. The chemical reactivity of fluoromethanes was compared with that of chloromethanes as alkylators of GSH. At pH 7.4 and 37 degrees C, a fluoromethane has 1/500th the reactivity of a chloromethane. A comparison of the rates of reaction of the fluoromethane with cathepsin B and with GSH at pH 6.4 revealed an enhancement of 10(8)-fold for the alkylation of the enzyme, ascribable largely to a proximity effect.